Strengthening Mortality Statistics for Health Programs in Malaysia: Lessons from the Field - Chalapati Rao; Mohammad Azahadi Omar; Shubash Shander Ganapathy; Nor Saleha Ibrahim Tamin (Dr. Sulaiman Al Habib Medical Journal)
Reliable information on causes of death is essential for an evidence-based health policy. There is a challenge in ascertaining the cause for deaths occurring without medical attention. This has been a persistent problem for Malaysia, where 50% of deaths are registered as “nonmedically certified” deaths mostly with ill-defined causes. During 2014–2016, a research study was conducted in a nationally representative sample of 15,000 deaths in Malaysia, to verify their registered causes and develop cause-specific mortality estimates. Standard Verbal Autopsy (VA) methods were used to ascertain causes for the nonmedically certified deaths in the sample. VA methods were successful in assigning specific causes for most cases with ill-defined causes of death, resulting in plausible mortality patterns. The Malaysian government issued official instructions for routine implementation of VA methods for nonmedically certified deaths. Nationwide capacity development was implemented to improve data quality. These activities provide several lessons for strengthening the national mortality statistics programs.